2022
DOI: 10.1007/s41959-022-00073-z
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering dominant characteristics for entrepreneurial intention and success in the last decade: systematic literature review

Abstract: This study presents a systematic literature review to identify dominant characteristics that predict entrepreneurial intention and entrepreneurial success in the twentyfirst century. The aim was to provide insights to entrepreneurs, academicians, policy makers, counsellors and all those charged with the responsibility of entrepreneurship development. The study applied a systematic review of the literature contained in the two databases, namely Semantic Scholar and Google Scholar. The analysis of the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…Ugwueze et al (2022) found that SE regulates the relationship between innovativeness and EI. Various studies confirm the influence of entrepreneurial motivation (EM) on EI development (Barba-Sánchez & Atienza-Sahuquillo, 2018;Farouk et al, 2014;Yangailo & Qutieshat, 2022).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Ugwueze et al (2022) found that SE regulates the relationship between innovativeness and EI. Various studies confirm the influence of entrepreneurial motivation (EM) on EI development (Barba-Sánchez & Atienza-Sahuquillo, 2018;Farouk et al, 2014;Yangailo & Qutieshat, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…Various studies confirm the influence of entrepreneurial personality traits (PT), such as risk-taking tendency (Hameed & Irfan, 2019;Sher et al, 2017), creativity and commitment (Raine & Pandya, 2019), locus of control (Farouk et al, 2014;Liñán & Chen, 2006;Yangailo & Qutieshat, 2022), lifelong learning (Hameed & Irfan, 2019), problem-solving (Sun et al, 2020), openness (Yangailo & Qutieshat, 2022;Yin & Liang, 2018), and innovativeness (Yangailo & Qutieshat, 2022) on EI development. However, other studies suggest insignificant evidence of PT influencing EI despite a positive correlation (Yin & Liang, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies that have used this methodology have followed the methodologies and strategies used by Tranfield et al (2003). Although various previous researchers have applied Tranfield et al's (2003) strategies, which include: planning the study, conducting a review, and reporting and disseminating the results, they have used different foci and databases to conduct their studies (see Yangailo & Qutieshat, 2022;Kigozi et al, 2019;Manatos et al, 2017;Yangailo & Kaunda, 2021;Tarí, 2011). This study adopted the very methodology and strategies applied by Tranfield et al (2003), based on the fact that they are reliable, transparent and unbiased (Papaioannou et al, 2010).…”
Section: Planning For Reviewmentioning
confidence: 99%
“…The present study was conducted to further explore this relationship by including 'transformational leadership' as a contingency variable to fill this gap. However, the railway industry, where this study was conducted, has not gotten much attention from researchers Yangailo & Kaunda, 2021;Yangailo & Mkandawire, 2023;Yangailo, 2022;Yangailo & Qutieshat, 2022;Yangailo & Mpundu, 2023;Yangailo, 2024). For this reason, the study is relevant.…”
Section: Purpose Of the Studymentioning
confidence: 99%